2012
DOI: 10.1523/jneurosci.6271-11.2012
|View full text |Cite
|
Sign up to set email alerts
|

LIM Domain Only 4 (LMO4) Regulates Calcium-Induced Calcium Release and Synaptic Plasticity in the Hippocampus

Abstract: The LIM domain only 4 (LMO4) transcription cofactor activates gene expression in neurons and regulates key aspects of network formation, but the mechanisms are poorly understood. Here, we show that LMO4 positively regulates ryanodine receptor type 2 (RyR2) expression, thereby suggesting that LMO4 regulates calcium-induced calcium release (CICR) in central neurons. We found that CICR modulation of the afterhyperpolarization in CA3 neurons from mice carrying a forebrain-specific deletion of LMO4 (LMO4 KO) was se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 60 publications
1
32
0
Order By: Relevance
“…Notably, Aβ 42 increases expression of LMO4, thus providing a direct mechanism for increased RyR2 in AD brains [6]. Likewise, knockout of LMO4 reduces RyR-mediated Ca 2+ signaling and reduces its facilitation of CA3-CA1 glutamatergic synaptic transmission and LTP [124]. Because the molecular and protein machinery are uniquely aligned for synaptic RyR2 expression, these collective findings reveal a previously unappreciated role of RyR2 dysregulation in AD pathophysiology and synaptic degeneration.…”
Section: Early Transcriptomic and Proteomic Evidencementioning
confidence: 99%
“…Notably, Aβ 42 increases expression of LMO4, thus providing a direct mechanism for increased RyR2 in AD brains [6]. Likewise, knockout of LMO4 reduces RyR-mediated Ca 2+ signaling and reduces its facilitation of CA3-CA1 glutamatergic synaptic transmission and LTP [124]. Because the molecular and protein machinery are uniquely aligned for synaptic RyR2 expression, these collective findings reveal a previously unappreciated role of RyR2 dysregulation in AD pathophysiology and synaptic degeneration.…”
Section: Early Transcriptomic and Proteomic Evidencementioning
confidence: 99%
“…Along with synaptic effects, we found that the RQ mutation significantly increased postspike AHP in cortical neurons. In the absence of increased GABA release, enhancement of the late AHP is likely due to increased activation of Ca 2+ -sensitive potassium (SK) channels (46). Increased neuronal AHP limits repetitive highfrequency firing and might explain why seizures are rare in the RQ mouse.…”
Section: Rq Mutation Selectively Enhances Excitatory Synaptic Transmimentioning
confidence: 99%
“…The IsAHP is manifested as a slow-rising and decaying outward current activated by the influx of calcium after the return of the membrane potential to À55 mV (1). In CA3 neurons, this calcium influx also triggers calcium-induced calcium release from internal stores, further prolonging the sAHP (30,31). We recorded the IsAHP in the presence of 100 nM apamin to block calcium-activated SK channels because their deactivation might have overlapped with the IsAHP activation.…”
Section: Kcnq3 Channels Are Critical For the Pyramidal Neuron Sahp Cumentioning
confidence: 99%